2012
DOI: 10.1242/jeb.059634
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanics meets the ecological niche: the importance of temporal data resolution

Abstract: SUMMARY The emerging field of mechanistic niche modelling aims to link the functional traits of organisms to their environments to predict survival, reproduction, distribution and abundance. This approach has great potential to increase our understanding of the impacts of environmental change on individuals, populations and communities by providing functional connections between physiological and ecological response to increasingly available spatial environmental data. By their nature, such mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
91
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 113 publications
(94 citation statements)
references
References 70 publications
1
91
0
Order By: Relevance
“…Repeated exposure to sublethal highs can be more detrimental to fitness than acute exposure to extreme temperatures for some species (Kearney et al . ; Marshall & Sinclair ). Thus, the effects of sublethal warming drive responses to warming through impacts on development and stage‐specific mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Repeated exposure to sublethal highs can be more detrimental to fitness than acute exposure to extreme temperatures for some species (Kearney et al . ; Marshall & Sinclair ). Thus, the effects of sublethal warming drive responses to warming through impacts on development and stage‐specific mortality.…”
Section: Discussionmentioning
confidence: 99%
“…This phase of the work was based on mechanistic ecophysiological (biophysical, BP;Helmuth 1998Helmuth , 1999 and bioenergetic (Dynamic Energy Budget, DEB; Kooijman 2010) models to estimate life history traits of target animals and to predict their distributions throughout study areas under current and future scenarios of increasing temperature in the context of climate change (see also Kearney et al 2010Kearney et al , 2012Kearney 2012;SarĂ  et al 2011bSarĂ  et al , 2012. Given the lack of sufficient baseline information for most of the organisms examined in the present study (also combining results from systematic reviews and new primary data), modelling could only be performed on mussels.…”
Section: Ecological Modellingmentioning
confidence: 99%
“…Temporally, recent studies have shown the importance of examining diurnal, seasonal and inter-annual time scales for understanding warming impacts across latitude [2,6,50,51]. In addition to altering performance curves [49], temporal variation can be critical for species in buffering climate change impacts, especially for species with limited behavioural thermoregulation capacity [52]. As shown in this study (figures 1 and 2), the variation in air temperature at different scales (minutes, hours, years) may not be entirely sufficient to characterize the thermal environment given the high variation in body temperature at these scales.…”
Section: Discussionmentioning
confidence: 99%